COMPARISON OF PHENOLIC CONTENT OF RED GINGER (Zingiber officinale var. rubrum Theilade) AT DIFFERENT GROWING LOCATIONS - Rizky, Alfira; Styawan, Anita Agustina (Jurnal Farmasi Sains dan Praktis, 2024)
Red ginger (Zingiber officinale var. rubrum Theilade) as a traditional medicine can be used as anti-inflammatory, analgesic, antipyretic, lower cholesterol, prevent impotence, depression, and others. The rhizome of the red ginger plant has different phenolic levels in each region. To find out the comparison of the levels of these compounds, an examination was carried out with UV-Vis’s spectrophotometry. The purpose of this research was to determine the comparison of phenolic content of red ginger from different growing locations, namely from Wonosobo Regency and Karanganyar Regency. This research used samples of red ginger extract (Zingiber officinale var. rubrum Theilade), as much as 500 grams of red ginger simplisia extracted using maceration method with 96% ethanol solvent in ratio of 1:5. Quantitative analysis phenolic content using UV-Vis’s spectrophotometry methode. The results of quantitative tests using UV-Vis’s spectrophotometry obtained a significant comparison of the total phenolic content of red ginger (Zingiber officinale var. rubrum Theilade) from Wonosobo Regency of 0.49% v/b and red ginger from Karanganyar Regency of 0.47% v/b